1999
DOI: 10.1007/bf02349851
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption behavior of rice husk for the decontamination of chromium from industrial effluents

Abstract: Rice husk, an agricultural waste product, was studied as a potential decontaminant for chromium in the effluents of leather tanning industries. Physico-chemical parameters such as selection of appropriate electrolyte, shaking time, concentration of adsorbent and adsorbate were studied to optimize the best conditions in which this material can be utilized on commercial scale for the decontamination of effluents.The radiotracer technique was used to determine the distribution of chromium. In certain cases atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
4
6
0
Order By: Relevance
“…It is clear from the results that maximum sorption occurred in deionized water while the sorption decreased with an increase in acid concentration. These results are in conformity with Hg (II) ions sorption onto sawdust (Hasany and Ahmad, 2002) and coconut husk and chromium onto rice husk (Khalid et al, 1999). The decrease in chromium sorption at higher acid concentration might be due to the competition of the proton and the positively charged chromium ions.…”
Section: Effect Of Electrolytessupporting
confidence: 87%
See 1 more Smart Citation
“…It is clear from the results that maximum sorption occurred in deionized water while the sorption decreased with an increase in acid concentration. These results are in conformity with Hg (II) ions sorption onto sawdust (Hasany and Ahmad, 2002) and coconut husk and chromium onto rice husk (Khalid et al, 1999). The decrease in chromium sorption at higher acid concentration might be due to the competition of the proton and the positively charged chromium ions.…”
Section: Effect Of Electrolytessupporting
confidence: 87%
“…Chromium, an important element from environmental point of view has been the subject of several studies wherein its accumulation on cheaper materials like flyashwollastonite (Pandy et al, 1984), zeolites (Foldesova et al, 2000), modified coconut husk (Low et al, 1997), rice husk (Khalid et al, 1999), Haro river sand (Hasany and Chaudhry, 1998), seed of leguminous crops (Voropanova et al, 1998) and modified rice husks (Lee et al, 1998) have been investigated. Chromium pollution is a serious problem facing our country due to the tannery industry.…”
Section: Introductionmentioning
confidence: 99%
“…RH exhibited highest adsorption capacity at pH 5.0. Similar tend was reported by Khalid et al [34] while employing rice husk as an adsorbent for chromium. The results demonstrated that the maximum adsorption capacity for RH occurred at pH 5.0, pH 2.0 was found optimum for Pd(II) ions adsorption on RHS-ED and RHS-DT while RHS exhibits maximum capacity at pH 2.5.…”
Section: Effect Of Phsupporting
confidence: 81%
“…In the present study, the decrease in the sorption of copper at higher acidic medium can be explained on the basic of competitive reaction of the protons in the medium and positively charged copper(II) ions. While small sorption of metal at low pH is in accordance with the concept of zero point charge (pHzpc) which lies in the range of 1.8-2.2 for SiO 2 (Khalid et al 1999). Also the sample may contain other organic compounds in Si-sample which the sorption may be due to the electrostatic attraction with the surface groups.…”
Section: Effect Of Phsupporting
confidence: 67%
“…This results in the formation of silica surface as weakly acidic. The cation exchange reaction can occur in aqueous solution as follows (Khalid et al 1999):…”
Section: Effect Of Phmentioning
confidence: 99%